PENGGUNAAN GOOGLE FORM SEBAGAI ALAT EVALUASI PEMBELAJARAN AKIDAH AKHLAK KELAS IV DI SD ISLAM BANI HASYIM - Anggi Laela Aprina Wardani; Ika Ratih Sulistiani; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This study aims to describe the google form as an evaluation tool for the fourth grade moral aqidah learning at SD Islam Bani Hasyim Singosari. The type of research conducted using descriptive qualitative research and technical collection using observation, interviews and documentation. The learning process carried out at SD Islam Bani Hasyim uses google form as an evaluation tool. The Bani Hasyim school uses this application because it is ease to use and can be accessed by anyone, both from school, offices and others. To use this application, you must have a g-mail first if you want to enter the google form account. The results obtained by the researchers regarding the use of google form as an evaluation tool at SD Islam Bani Hasyim are that many children are easier to understand and more enthusiastic in implementing learning evaluations. The advantages of this application when learning morals are that there are many variants of images and can send any video. The drawback of this application is that it cannot be used in both directions.